2017
DOI: 10.1515/jcim-2015-0081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electro-acupuncture on pro-oxidant antioxidant balance values in overweight and obese subjects: a randomized controlled trial study

Abstract: Objective To undertake a randomized controlled trial in 196 obese subjects to examine the effect of electro-acupuncture on serum pro-oxidant antioxidant balance (PAB) values. Methods Subjects received authentic acupuncture (cases) or sham acupuncture (controls) for 6 weeks in combination with a low-calorie diet. In the following 6 weeks, they received the low-calorie diet alone. Serum PAB was measured at baseline, and 6 and 12 weeks later. Results We found that serum PAB values decreased significantly in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Generally, improvements of diet and lifestyle are recommended; however, the effect on weight loss is often unsatisfactory. A large body of clinical and experimental evidence shows that acupuncture is effective for the treatment of obesity, and that acupuncture treatment is accompanied by a reduction in obesity-related com-plications, such as hyperlipidemia[ 21 , 22 ]. Indeed, in this study, the AG mice were observed to have lower body weight and less abdominal adiposity with an improved blood lipid status, in comparison to NG mice.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, improvements of diet and lifestyle are recommended; however, the effect on weight loss is often unsatisfactory. A large body of clinical and experimental evidence shows that acupuncture is effective for the treatment of obesity, and that acupuncture treatment is accompanied by a reduction in obesity-related com-plications, such as hyperlipidemia[ 21 , 22 ]. Indeed, in this study, the AG mice were observed to have lower body weight and less abdominal adiposity with an improved blood lipid status, in comparison to NG mice.…”
Section: Discussionmentioning
confidence: 99%
“…In obese subjects, acupuncture treatment significantly decreased serum pro-oxidant antioxidant balance (PAB) values, which has been shown to be positively correlated to body weight and also increased in obese patients [34]. Eight acupuncture points on the abdomen, including Tianshu (ST-25) bilateral, Weidao (GB-28) bilateral, Zhongwan (REN-12), Shuifen (REN-9), Guanyuan (REN-4), Sanyinjiao (SP-6), and additional points including Quchi (LI-11) and Fenlong (ST-40) for excess mood (patients with higher energy) and Qihai (REN-6) and Yinlingqau (SP-9) for deficiency mood (patients with lower energy) on both lower legs, were selected.…”
Section: Evidence From Clinical Studiesmentioning
confidence: 99%
“…In particular, there is experimental evidence that acupuncture not only reduces body weight, but also increases adiponectin and decreases leptin in obese rats (Peplow, 2015). This is supported by the results of clinical trials which show that acupuncture can reduce not only body weight and fat content, but also obesity-related complications, such as serum pro-oxidant antioxidant imbalance, dyslipidemia, and inflammation (Mazidi et al, 2017). Another interesting experimental finding is that electro-acupuncture (EA) increases cold endurance in the Stat5NKO mouse model of obesity (Fu et al, 2017).…”
Section: Introductionmentioning
confidence: 81%